NUTRITIONAL CONTENT, PHYTOCHEMICALS AND IN-VITRO ANTIOXIDANT ACTIVITIES OF ETHANOL EXTRACT OF RED AND WHITE ONION - Laminu, Hauwa Hajjagana; Buba, Fatimah; Dibal, Nathan Isaac; Abana, Rakiya; Mamza, Zamdai Yusuf; Manye, Sunday Joseph; Hassan, Abdulfatah Alhaji; Ishaku, Barka (FUDMA JOURNAL OF SCIENCES, 2024)
Since antiquity onions (Allium cepa, L) have been cultivated across the globe as an important source of food and medicine. The study evaluated the nutritional content, phytochemistry and invitro antioxidant activities of ethanol extract of red and white onion bulbs. Red and white onion bulbs were purchased from a Local market in Maiduguri. Ethanol extracts were prepared using homogenized bulb. The proximate analysis, flavonoids, tannin, and phenol contents of the extracts as well as the antioxidant activities (total antioxidant activity, reducing power, and 1,1-Diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activities) were evaluated using standard procedures. The ash and carbohydrate contents of the two extracts were similar. However, the fat and protein contents were higher in white onion (2.44% & 1.05%) compared to the red onion (1.00% & 0.13%) while the moisture content was higher in red onion (16.10%) compared to the white onion (13.60%). The flavonoids, tannin, and phenol content as well as the total antioxidant activity was significantly higher (p<0.05) in the red onion relative to the white. White onion had a better reducing power activity compared to the red while the red had higher DPPH free radical scavenging activity compared to the white. Conclusively, our findings revealed that both red and white onion contains varying quantity of phenolic compounds with strong reducing power and DPPH free radical scavenging activity. However, red onion was shown to have higher antioxidant activity relative to the white.